The Role of Islamic Education in Shaping Indonesian National Identity - Bertuah, Muhammad Fauzi (International Journal of Applied Educational Research (IJAER), 2023)
There is a strong connection between the Indonesian National Identity and Islamic Education, which is influenced by Indonesia's anthropological conditions and the majority Islamic population. The country was historically known as the Dutch East Indies, before the Youth Pledge movement paved the way for the formation of the Indonesian Nation. After gaining independence from Dutch colonialism, Indonesian leaders sought to construct the nation's identity. They established four pillars of character: Pancasila, the 1945 Constitution, Bhinneka Tunggal Ika, and the Unitary State of the Republic of Indonesia. In formulating the nation's Pancasila character, they embraced the values taught in Islamic teachings, including those found within the Quran. To promote character education throughout the community, the Indonesian government provides educational programs that cover these values. Arguments can be developed through qualitative research to explain the connection between the Indonesian National Identity and Islamic Education. The journal article examines the concise history of civilization and the nature of the Indonesian nation, in addition to exploring its connection with Islamic Education.